Features of the phraseology units used in literary texts of Kazakh and English languages (Eurasian Journal of Philology Science and Education, 2018)
The article considers the scope and peculiarities of the using phraseological units in Kazakh and English languages. Besides it also analyzes the semantics, structures and expressive-stylistic aspects of phraseology. The authors gave the examples of works of Kazakh and English writers. In the article the authors explore the phraseological fund of the artistic language, on the one hand to learn more about the periodicity of the national language, in another sense to discover the linguistic skill of each writer and to determine its role in the development of the literary language. It also notes that phraseology is one of the most powerful language tools that can justify the aesthetic taste of the people in reducing the need for fiction.The national differences by phraseological units in double language have been relatively reviewed in the article.